SINERGITAS LEMBAGA PENDIDIKAN DENGAN DUNIA USAHA/INDUSTRI DALAM MENINGKATKAN MUTU LULUSAN SMK - Hidayat, Arif (PT. Solusi Komunikasi Terapan, 2023)
The synergy between educational institutions and DUDI does not work optimally, which causes the absorption capacity of vocational school graduates to remain low. The demand for increased competitiveness through the quality of work-ready graduates, where graduate output and outcomes are a priority. The general aim of this research is to determine and analyze the synergy of educational institutions with DUDI in improving the quality of vocational school graduates. The specific objectives of this research are (1). Know and explain policies and programs with DUDI in improving the quality of graduates; (2). Implementation and results with DUDI in improving the quality of graduates; (3). Problems and weaknesses faced with DUDI in improving the quality of graduates; (4). Future trends and demands with DUDI in improving the quality of graduates; (5). Efforts and steps for future improvements with DUDI in improving the quality of graduates. The research was carried out using a case study approach at SMK Lentera Bangsa 1 Karawang, SMK Nurul Ansor Karawang and SMK Lentera Bangsa 2 Karawang using qualitative methods. The conclusion of this research is that there is a common goal through the synergy of educational institutions with DUDI, the synergy of educational institutions with DUDI has improved the quality of graduates absorbed. The synergy helps vocational school graduates be ready for work and makes it easier for companies to recruit quality graduates. The synergy of educational institutions with DUDI has an impact on improving the quality of graduates both in terms of input, process, output and outcome.